(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
This study was conducted to assess the environmental status of leishmaniasis in Brak and its surrounding areas. The locations of infection were identified based on patient records from health units in the Brak region. Sample collection took place from the beginning of September to the end of December 2023 through field visits to areas where initial cases of leishmaniasis were reported, specifically Ishkida, Brak, and Tamzawa. These visits were carried out in collaboration with the Rapid Response and Surveillance Team, with each area being visited three times. Regarding vector collection, sand flies were captured using traditional sticky paper traps. These traps were deployed in mosquito-prone zones, suspended from plant branches at a height not exceeding 1 meter above ground level. The collected insects were identified and classified accordingly. For rodent sampling, Tongde-brand sticky traps were used. These traps featured adhesive layers on both sides and were baited with attractants specific to rats and mice. The findings indicate that the study area is endemic for the sand fly vector responsible for transmitting leishmaniasis. The environmental conditions in the region are conducive to the proliferation of wild rodents that act as reservoirs for Leishmania parasites, as well as to the survival and distribution of associated insect vectors. Transmission typically occurs when female sand flies feed on the blood of animals and humans. The results of the current study align with those reported by the Libyan Center for Disease Control and Surveillance in 2021, which documented leishmaniasis cases in Ishkida and Brak. Sand flies were observed 6 and 4 times respectively in Ishkida and Brak. However, the findings did not align with Tamzawa, where no sand flies were recorded. The entomological survey in the study regions revealed the presence of various insect species, including mosquitoes, moths, fleas, lice, tsetse flies, “Tanfush” bugs (likely local naming), house flies, ants, grain moths, and hide beetles. In addition, rodents—recognized reservoirs of the parasite—were observed in Ishkida and their traces were detected in Brak. However, no rodents or their traces were found in Tamzawa during the collection period. In conclusion, the study area is confirmed as an endemic zone for the sand fly vector of leishmaniasis, with favorable environmental conditions for the persistence and proliferation of rodent reservoirs and associated insect vectors, whose distribution is closely linked to the presence of the sand fly.